Export structure and export specialisation in Central and Eastern European countries - Zsuzsa Munkácsi (Magyar Nemzeti Bank, 2009)
Before the millennium Hungary's market share in exports of goods was increasing at the fastest rate in Central and Eastern Europe; however, after 2000 that growth became the lowest. The slowdown in growth in Hungary's export market share is mainly due to the stagnating price index of goods exports. The aim of this paper is to examine whether this process was caused by reaching an equilibrium or structural factors. In the paper the exports of goods structure (by product, country, technology, skill and intensity), the relationship between export specialisation and export price indices, and the role of import demand in specialisation are examined for the Visegrad Group and Romania in the periods 19951999 and 20002007. The results imply that the stagnation of Hungarian goods export prices is partly natural and partly brought about by structural factors.
Keywords: F10; F14; 330; exports; export structure; specialisation; Export; Außenhandelsstruktur; Außenhandelspreis; Internationale Arbeitsteilung; Visegrad-Staaten; Rumänien